Multidisciplinary team actions of a Brazilian Psychosocial Care Center for Alcohol and Drugs - Liana Longo Teixeira Lopes; Mara Regina Santos da Silva; Alessandro Marques dos Santos; Jacqueline Flores de Oliveira (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to investigate the criteria used by health professionals to identify the phase of consumption of alcohol and drug users, and actions directed to their care. Method: a qualitative study developed with 14 professionals from a Brazilian Psychosocial Care Center for Alcohol and Drugs (Centro de Atenção Psicossocial Álcool e Drogas) based in the south of the country. Data were collected in June 2017 through semi-structured interviews and then submitted to thematic analysis. Results: the criteria used by the professionals were: periodicity of use; amount and type of drug used; repercussions of misuse; and place that the drug occupies in the person's life. The actions developed were orientation and referral to support groups, therapeutic workshops and individual care. Final considerations: the chronic nature of alcohol/drug use/dependence requires specific care in each phase, and objective criteria to identify and intervene in early phases, aiming at the prevention of chemical dependence.